2011
DOI: 10.1145/2043164.2018484
|View full text |Cite
|
Sign up to set email alerts
|

What can free money tell us on the virtual black market?

Abstract: ABSTRACT"Real money trading" or "Gold farming" refers to a set of illicit practices for gathering and distributing virtual goods in online games for real money. Unlike previous work, we use network-wide economic interactions among in-game characters as a lens to monitor, detect and identify gold farming networks. Our work is based on a set of real ingame trade activity logs collected for one month in year 2010 from the world's second largest MMORPG called AION (with 3.4 million subscribers). This is the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…We assume that game bots have roles [9,1]. For instance, some game bots are responsible for gold farming, while other game bots gather game money and items from gold farmers or sell them for real money [25].…”
Section: Network Measuresmentioning
confidence: 99%
“…We assume that game bots have roles [9,1]. For instance, some game bots are responsible for gold farming, while other game bots gather game money and items from gold farmers or sell them for real money [25].…”
Section: Network Measuresmentioning
confidence: 99%
“…Consequently, the standard deviation of the degree in this type is very high, while degree assortativity is close to -1 (see Fig. Previous studies [19,20,33] showed that gold farming groups tend to construct communities similar to this type. e reasoning why this type is a gold farming group follows.…”
Section: Rmt Group Detectionmentioning
confidence: 72%
“…is is proof that analyzing a community network in an online game can assist in understanding a real world community structure. Woo et al [33] analyzed the free money trade referring that people only give game money without ge ing any goods in return for GFG detection. Fujita et al [11] proposed a RMT detection method based on the observation that RMT traders tend to form dense relationships with each other.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…-"Bot Detection Based on Social Interactions in MMORPGs" [21] Adaboost [8], [18], [21], [33] -Low error rate and Fast computation speed -Sensitiveness in noise data -"Mining for gold farmers: Automatic detection of deviant players in mmogs" [33] Neural Network [18], [27], [45] -High accuracy and lots of computation time because of lots of computation quantities -Difficult to interpret grounds of result -"The ones that got away: False negative estimation based approaches for gold farmer detection" [18] Character travel path [6], [11], [26], [37], [48] -Easy to classification because of difference of travel path each to each -Requiring differential application depending on using map -"Second life: a social network of humans and bots" [10] User behavior [13], [28], [36][37], [41][42], [46] -Easy to classification because of difference of Window event between normal user and abnormal user -Requiring client module to analysis -"An automatic and proactive identity theft detection model in MMORPGs" [36] Social network [7], [8], [10], [18], [20][21], [27], [29], [30][31], [39] -Applicable in online game, easy to classification between normal user and abnormal user -Difficult to classification between normal user and abnormal user in solo play game -"Battle of botcraft: fighting bots in online games with human observational proofs" [27] Network traffic [43]…”
mentioning
confidence: 99%